Effect of sorbitol and 6-BAP in Swietenia mahagoni (L.) Jacq. somatic embryos maturation and germination - Raúl Barbón; Iván Borroto; Mariana la O; Elisa Quiala; Marta Pérez (Biotecnología Vegetal, 2013)
Low germination of somatic embryos in S. mahagoni is a problem that needs solutions. Its cause is related to the low level of embryo maturation. The objective of this research was to determine the effect of different concentrations of sorbitol and 6-BAP in the maturation of somatic embryos of S. mahagoni to increase the percentage of germination. Somatic embryos in cotyledonary stage were placed in maturation medium. Three concentrations of sorbitol (20.0, 40.0 and 60.0 g l-1) were used and the maturation of the embryos was assessed by their response to the germination medium. It was shown that somatic embryos growing in a culture medium for the maturation with sorbitol 40 and 60 g l-1 in combination with 6-BAP (0.25 mg l-1) is necessary to increase the number of somatic embryos germinated in Swietenia mahagoni (L) Jacq.